Rainfall intensity duration frequency analysis - KOTHYARI , U. C.; VERMA, S. K.; GARDE, R. J. (MAUSAM, 1990)
In the present study the analysis of rainfall data compiled for eighty stations spread over several parts of India has been carried out for developing a general relationship for the estimation of short duration rainfall intensity.